Rescue of follicle development after oocyte-induced ovary dysfunction and infertility in a model of POI - Sheikh, Sairah; Lo, Belinda K. M.; Kaune, Heidy; Bansal, Jassimran; Deleva, Anna; Williams, Suzannah A. (Frontiers in Cell and Developmental Biology, 2023)
Premature ovarian insufficiency (POI) affects 1% of women under 40 years of age with little understanding of the etiology since >74% of cases are idiopathic. To explore how oocyte quality contributes to POI, we use a mouse model with follicular POI due to oocyte-specific gene modification. These studies reveal that the oocyte is capable of rendering ovarian somatic cells dysfunctional leading to an environment that is nonconducive to follicle development. This study demonstrates that ovary dysfunction can be induced by abnormal oocytes, however, germ cells retain the ability to develop normally and by altering the somatic cell environment -follicle development can be restored. Our results highlight that defective oocytes can cause ovarian dysfunction but that such infertility does not need to be irreversible and may lead to new clinical treatments.